Two-photon absorption within layered Bi2Te3 topological insulators and the role of nonlinear transmittance therein. Issue 23 (22nd May 2019) - Qiao, Junpeng; Chuang, Meng-Yuan; Lan, Jia-Chi; Lin, Yuan-Yao; Sung, Wei-Heng; Fan, Ranran; Wu, Meng-Yu; Lee, Chi-Yang; Chen, Chun-Hu; Liu, Hong; Lee, Chao-Kuei
Abstract : In this study, strong two-photon absorption (TPA) in a layered bismuth telluride (Bi2 Te3 ) topological insulator (TI) is observed and investigated by the Z-scan method under excitation with a femtosecond laser pulse at a wavelength of 1056 nm. Abstract : In this study, strong two-photon absorption (TPA) in a layered bismuth telluride (Bi2 Te3 ) topological insulator (TI) is observed and investigated by the Z-scan method under excitation with a femtosecond laser pulse at a wavelength of 1056 nm. Nonlinear transmission measurements reveal that Bi2 Te3 possesses not only the property of single photon absorption (SPA) but also the effect of TPA. A saturation TPA coefficient as high as ∼2.29 × 10 6 cm GW −1 has been obtained, which is at least two orders of magnitude higher than that of other two dimensional (2D) materials, such as MoS2 . The large TPA effect in the Bi2 Te3 TI is attributed to the existence of high-lying bulk states located above the first bulk state. Meanwhile, it can also be used to explain the discontinuity of the optical nonlinear transmittance between the low and high excitation energy regions.